Pengaruh Disiplin Kerja, Motivasi Kerja dan Kompensasi Terhadap Loyalitas Pegawai PT Kreasi Kuliner Kondang Di Yogyakarta - Ahmad Dzulfikri Karim (JURNAL EKOBIS DEWANTARA, 2020)
The purpose of the research was to test the influence of work discipline, work motivation, and compensation toward the employee loyalty of PT Kreasi Kuliner Kondang. In sampling the researchers used a saturated sample with 70 respondents. Data analysis techniques using is multiple linear regression analysis. This study state that work dicipline has a significant positive effect on employee loyalty, work motivation has a significant positive effect on employee loyalty and compensation has a significant positive effect on employee loyalty.